Análise de robustez de estações da rede GNSS-SP - Cavalheri, Emerson Pereira [UNESP]; Chaves, João Carlos [UNESP] (Universidade Federal do Paraná, 2014)
Currently, the need of reliable coordinates has been one of the main objectives of the scientific and practice community. Thus, the robustness analysis of a geodetic network, aims, at analyzing if the network is robust or not, based on the maximum undetectable errors. The network will be robust if the influence of these errors is small, otherwise it is weak, or not robust. This analysis is performed with the merger of two techniques, one which deals with the statistical analysis of reliability and the other one with the geometric strength analysis. The reliability analysis will provide the maximum error that cannot be detected by tests, after the adjustment. After finding these errors, the geometric strength analysis will determine the potential strain that the network will have, based on these errors. It is emphasized that the robustness analysis doesn't depend of the datum, reflecting only the geometry of the network and the accuracy of the observations (VANÌCEK et al., 2001). Therefore, this work aims at contributing to the scientific research on geodetic networks, checking the same, based on their geometry and observations.

Atualmente, a necessidade de coordenadas confiáveis tem sido um dos objetivos da comunidade científica e prática. Desta forma, a análise de robustez de uma rede geodésica, tem como objetivos, com base nos erros máximos não detectados, analisar se a rede é robusta ou não. A rede será robusta se a influência destes erros for pequena, caso contrário é fraca, ou seja, não robusta. Esta análise se faz com a fusão de duas técnicas, uma que trata da análise estatística de confiabilidade e outra sobre a análise geométrica de deformações. A análise de confiabilidade fornecerá o erro máximo que não pode ser detectado por testes, após o ajustamento. Depois de encontrar estes erros, a análise geométrica de deformações determinará o potencial de deformação que esta rede terá com base nestes erros. Ressalta-se, ainda, que a análise de robustez não é dependente de datum, refletindo somente na geometria da rede e na acurácia das observações (VANÌCEK et al., 2001). Portanto, este trabalho tem como propósito contribuir com as investigações científicas sobre redes geodésicas, checando a mesma, com base em sua geometria e observações.
Robustness analysis of stations from the GNSS-SP network
Keywords: Robustez; Confiabilidade; Deformação; Robustness; Reliability; Strain